Wearable magnetoencephalography - Boto, Elena (2019)
Functional neuroimaging offers a means to understand brain function and dysfunction. Over decades, different technologies have been developed to provide a non-invasive measure of brain activity that could help us to better understand the mechanisms underlying human cognition. Magnetoencephalography (MEG) is one of these techniques which, over the past 30 years, has been increasingly contributing to neuroscientific studies giving insights into human brain electrophysiology, with excellent temporal resolution and surprisingly high spatial resolution. However, MEG hardware has limitations and it has only been in the past few years that alternative technologies have seen a rapid progress with an intent to overcome the drawbacks of conventional MEG devices. The main limitation of MEG systems is that they rely on superconducting quantum interference devices (SQUIDs) to measure magnetic fields outside the head. This means that they require cryogenic cooling and as a consequence, sensors are fixed in position in a one-size-fits-all helmet. A vacuum is maintained between the subject’s head and the detectors which limits the sensitivity of the measurement, and subjects must remain still in large cumbersome scanners.